Forage agriculture and Milk Geography in Mexico: Itineraries and Imponderables of the Green Revolution in the State of Mexico, 1936-1970 (Quinto Sol, 2023)
The article studies how, between 1950 and 1970, the Office of Special Studies, an institution co-financed by the Mexican government and the Rockefeller Foundation, participated in the formation of an intensive forage agriculture, as well as in the reorganization of the Mexican dairy geography. To do this, we will address the case of the State of Mexico, an entity that until 1936 supplied milk to Mexico City, the capital of the country and the main center of demand. In the following decade, however, drought, foot-and-mouth disease and increased demand created a bottleneck supply. To boost forage and milk production, the Office conducted research on alfalfa and corn in that state. However, the reconversion of the northern economy from cotton to milk in the 1950s, as well as the metropolitan expansion of Mexico City, gave way to the deal with Mexiquense agronomic and productive projects. In the 1970s, milk from the north of the country supplied most of the demand in Mexico City.
Keywords: agraria history; forages; technology